G-O vulnerability forecasting model and its improvement based on loss - Shi PENG; Hao GUO; Tao WANG (Dianxin kexue)
Each index to measure the vulnerability was analyzed.A mathematical definition of strong security was proposed,and the loss measurement and forecasting of vulnerability were used to solve the problem of software dependability uniform dimension.At the same time,loss occurrence law and the number of vulnerabilities found similarities between the law were discussed,to determine whether the use of software defect prediction model to predict the amount of loss.By referring to the classical G-O model,the predictive model of software loss was established,namely model was developed to predict the loss of G-O based vulnerabilities,and the accuracy of the model and the practicability of the test by using the actual data in the vulnerability database.